Synthesis and Biological Evaluation of 1,3,4-Oxadiazole Derivatives as Novel Analgesic and Antiinflammatory Agents - Chavan, R.S.; Nirmal, D.A.; Bhosale, A.V. (Asian Journal of Chemistry, 2011)
A novel series of 4-(2-(4-(5-(4-substituted phenyl)-1,3,4-oxadiazol-2-yl)phenylamino)ethoxy)- 2H-chromen-2-one (7a-j) have been synthesized from 4-(5-(4-substituted phenyl)-1,3,4- oxadiazol-2-yl)benzenamine (4a-j) and 4-(2-bromoethoxy)-2H-chromen-2-one (5). The synthesized compounds were characterized on the basis of their spectral (IR, 1H NMR) data and evaluated for the antiinflammatory and analgesic activity by using different pharmacological models. The most active compounds were subjected to acute ulcerogenesis activity and were found to be less ulcerogenic than the standard.